증강현실 기반 언어치료 프로그램이 자폐성장애 아동의 의문사 습득에 미치는 효과 - 김영익(Young Ik Kim); 권순복(Soon Bok Kwon); 권순우(Soon Woo Kwon); 팽재숙(Jae Sook Paeng) (언어치료연구, 2019)
목적: 본 연구는 4차 산업혁명 시대 스마트 융합의 첨단 기술을 언어치료 현장에 적용해보고자 한다. 이를 실현하기 위해 동적 움직임을 표현할 수 있는 증강현실 기반 언어치료 프로그램의 매체 개발을통하여 자폐성장애 아동의 의문사 습득 중재에 대한 효과를 알아보는데 그 목적이 있다. 방법: 연구의대상아동은 10~16세 자폐성장애 아동 3명으로 주 2~3회기, 총 18주(33회기) 기초선, 중재, 일반화, 유지 단계로 중재를 실시하였다. 매 회기 개별적으로 연구자와 아동이 1:1로 진행하였으며, 중재는증강현실 기반의 언어치료 프로그램을 태블릿 PC를 이용하여 그림카드 인식이 가능한 어플리케이션구현으로 68개의 장면 제시를 통한 의문사 총 145개의 문항으로 실시하였다. 의문사 습득의 평가는 매회기 12개의 문항에 대하여 ‘누가 3문항, 무엇(뭐) 6문항, 어디 3문항’으로 구성하여 의문사 습득정반응률로 살펴보았다. 결과: 대상아동 모두 기초선 단계와 비교하여 중재 단계에서는 매 회기가 진행될 때마다 의문사 습득의 정반응률이 증가하였으며, 일반화 단계와 유지 단계에서 또한 향상된 결과를확인할 수 있었다. 결론: 자폐성장애 아동의 장점인 시각을 통한 증강현실 기반 언어치료 프로그램은학습자 특성에 적합하고 동적인 움직임을 3D 입체영상으로 보여주어 의문사 습득을 위한 매체로는매우 효과적이다. 증강현실은 현실을 배경으로 하여 제시되는 다양한 장면에 대하여 실감나는 학습으로자연스러운 몰입과 주의집중을 이끌어 내는 것으로 나타났다. 따라서 언어치료 장면에서 목표 언어를습득하는데 효과적인 결과를 기대할 수 있을 것이다. Purpose : This study aims to apply advanced technology of smart convergence in the fourth industrial revolution era to the speech therapy field. The purpose of this study is to investigate the effects of an augmented reality-based speech therapy intervention on children with autistic disabilities. Methods : The subjects of the study were three children ranging in age between 10 and 16 with autistic disabilities who were given two or three sessions a week for a total of 18 weeks (33 sessions) including intervention into the baseline, intervention, generalization and maintenance stage. Each session consisted of 1:1 researchers and children, and the intervention was an application of an augmented reality-based language therapy program using a tablet PC to recognize picture cards. Respectively, the evaluation of the interrogatives acquisition consisted of the interrogatives, which consisted of 3 who items, 6 what items, and 3 where items. Results : Compared with the baseline level of all subjects, a positive response rate of the acquisition of the unexperienced person increased with each session in the intervention stage, and the improved results were also confirmed in the generalization and maintenance stages. Conclusions : The augmented reality-based speech therapy program, which is an advantage for children with autistic disabilities, is suitable for learner characteristics and shows dynamic movements as 3D stereoscopic images. The augmented reality showed natural immersion and attention by realistic learning about various scenes presented realistically. Therefore, we can expect effective results in acquiring target language. KCI Citation Count: 10